The Influence of Health Consciousness, Environmental Concern, and Theory of Planned Behavior (TPB) on the Intention to Purchase Organic Food - Tsakni, Georgia; Tsaknis, John; Tsaknis, Panagiotis; Tsakni, Aliki; Sahinidis, Alexandros; Kavoura, Androniki; Briciu, Victor-Alexandru; Briciu, Arabela (Springer, 2025)
The purpose of this paper is to examine the effects of health consciousness environmental concern and the factors of the Theory of Planned Behavior (TPB) (attitude, subjective norms, and perceived behavioral control) on the intention to purchase organic food. The data for this study were collected using a question-naire that contained 18 items. A convenient sample of 210 Greek individuals was included in the study (among the 1000 employees of a Greek university). Data anal-ysis was conducted using SPSS version 24 and Jamovi. Results illustrate that health consciousness affect indirectly and positively the intention to purchase organic food through attitude. Attitude, subjective norms, and perceived behavioral control have a positive and direct relationship with intention to purchase organic food. Further-more, health consciousness and environmental concern affect positive attitude. This study can provide insight into the key factors that contribute to the intention to buy organic food. In different contexts, additional variables may enhance the validity of these findings, and latent variables might confound them. Based on the findings of this study, society, organizations, and policy makers could support organic food producers.